FROM CHINESE FOLK RELIGION TO TRIDHARMA: THE TRAJECTORY OF CHINESE RELIGION IN INDONESIA - Aditya, Refan (Paradigma: Jurnal Kajian Budaya, 2025)
This article explores the trajectory of Chinese folk religion and the institution of klenteng (Chinese temple) within the broader discourse of Chinese religion in Indonesia, spanning from the colonial period to the post-reform era. Employing a historical and anthropological approach, this study examines Chinese religious discourse through Chinese-peranakan publications from the colonial era. It presents contemporary practices of Chinese folk religion and temple life as part of that evolving discourse. Historically and anthropologically, Chinese folk religion has been deeply embedded in the religious life of Chinese communities. However, its resonance has gradually degraded under the dominating religious narratives, particularly due to Christianisation during the colonial era and anti-Chinese politics, as well as religious governance in post-Independence Indonesia. This article takes the case of Muntilan, Central Java, to highlight a distinctive local expression of Chinese folk religion and klenteng culture that diverges from patterns found in major urban centres across Indonesia. This study reveals how Chinese folk religion, though marginalised by both state and elite religious institutions, persists through local ritual practices and temple communities, offering a critical perspective on religious categorisation and state power in postcolonial Indonesia.